2006
DOI: 10.5713/ajas.2006.418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lacquer (Rhus verniciflua) Supplementation on Growth Performance, Nutrient Digestibility, Carcass Traits and Serum Profile of Broiler Chickens

Abstract: This experiment was conducted to explore the efficacy of lacquer (Rhus verniciflua) supplementation on growth performance, nutrient digestibility, carcass traits and serum biochemical values in commercial broilers. Eight hundred and forty Hubbard broiler chicks (1d old) were randomly distributed and allotted to four dietary treatments for five weeks. Each treatment had 5 replicates with 42 birds each. The dietary treatments were (1) control (2) 1% lacquer, (3) 2% lacquer and 4) 4% lacquer supplied as meal in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
3
9
1
1
Order By: Relevance
“…The experimental diets were made isoenergetic by replacing parts of maize by animal fat in diets incorporated with lacquer meal and thus the ether extract was higher in these diets than control diets. Similar to the findings of the current study, no growth performance benefits were reported in broilers (Lohakare et al, 2006) and finisher pigs when their diets were supplemented with lacquer meal at 20 and 40 g/kg diet.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The experimental diets were made isoenergetic by replacing parts of maize by animal fat in diets incorporated with lacquer meal and thus the ether extract was higher in these diets than control diets. Similar to the findings of the current study, no growth performance benefits were reported in broilers (Lohakare et al, 2006) and finisher pigs when their diets were supplemented with lacquer meal at 20 and 40 g/kg diet.…”
Section: Discussionsupporting
confidence: 79%
“…In broilers, inclusion of lacquer meal did not have any effect on growth performance, but improved fat digestibility and reduced serum levels of cholesterol and triglyceride (Lohakare et al, 2006). In our previous study, lacquer meal added to the finisher diets of pigs at 20 and 40 g/kg reduced back fat and improved oxidative stability of meat but there was no effect on the growth performance and carcass traits .…”
Section: Introductionmentioning
confidence: 99%
“…Nurhayati et al (2005) reported that chickens were offered 0, 2.5, 5.0, 7.5 and 10% of pace meal had similar (P>0.05) feed consumption and pace meal did not significantly (P>0.05) increase feed consumption. Lohakare et al (2006) reported that lacquer is usually used as traditional medicine by Japanese, Chinese and Korean. There was no different effect among 0, 1, 2 and 4% of lacquer meal on increasing broiler feed consumption.…”
Section: Feed Consumptionmentioning
confidence: 99%
“…Sebagaimana dinyatakan oleh Lohakare et al (2006). bahwa herba dan tanaman obat mempunyai pengaruh terhadap pencernaan dan efisiensi pemanfaatan zat makanan pada ayam broiler.…”
Section: Pertambahan Bobot Badanunclassified